On recognition and respect: Honneth, intersubjectivity and education - Mark Murphy (Educational Futures)
While relatively unknown in education circles, the work of Axel Honneth, Director of the Institute of Social Research in Frankfurt (site of the famous Frankfurt School), is starting to gain prominence in Sociology, Political Science and Philosophy. The interest in his work revolves primarily around his theory of recognition, and how it situates itself in comparison to other theorists such as Charles Taylor and Nancy Fraser. In summary, these theorists argue that the drive towards personal autonomy can only be achieved intersubjectively – through the process of recognition from significant others.